2021
DOI: 10.1093/intqhc/mzab140
|View full text |Cite
|
Sign up to set email alerts
|

Defining value in health care: a scoping review of the literature

Abstract: Background As health-care spending rises internationally, policymakers have increasingly begun to look to improve health-care value. However, the precise definition of health-care value remains ambiguous. Methods We conducted a scoping review of the literature to understand how value has been defined in the context of health care. We searched PubMed, Embase, Google Scholar, PolicyFile and Scopus between February and March 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The choice of corticosteroid extends beyond the clinical data as healthcare costs are also important. A detailed discussion surrounding costs is out of the scope of this review, but with governments and other payers increasingly struggling to cover the costs of expensive new treatments [59], this subject is important to acknowledge. Deflazacort is markedly more expensive than prednisone in the US [60], but it is also associated with pharmacological and clinical benefits, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of corticosteroid extends beyond the clinical data as healthcare costs are also important. A detailed discussion surrounding costs is out of the scope of this review, but with governments and other payers increasingly struggling to cover the costs of expensive new treatments [59], this subject is important to acknowledge. Deflazacort is markedly more expensive than prednisone in the US [60], but it is also associated with pharmacological and clinical benefits, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus on the precise meaning of low-value care. It has been shown that health care providers often associate low-value care with services that do not show significant clinical benefit while also failing to give sufficient consideration to the associated costs [10][11][12] . This conceptual confusion has hindered the task of reducing low-value care in practice 11,13 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, this generic definition needs to be detailed in the preoperative field to guide the de-implementation of LVC. [10][11][12] This period is complex and presents a variety of situations and interpretations that may or may not be considered LVC and that need to be detailed. 3,5,13,14 LVC in the preoperative setting has many gaps: there is a few studies with the types of services and/or care beyond preoperative exams that do not add value; it is unknown whether this care positively or negatively impacts clinical outcomes in patients with intermediate or high-risk surgery; the scientific evidence at this moment is not comprehensive enough for LVC in this field and this problem has seen only moderate improvements over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…LVC is broadly defined as services that provide little or no benefit to patients that justify the cost or can even cause harm 9 . Furthermore, this generic definition needs to be detailed in the preoperative field to guide the de‐implementation of LVC 10‐12 . This period is complex and presents a variety of situations and interpretations that may or may not be considered LVC and that need to be detailed 3,5,13,14 .…”
Section: Introductionmentioning
confidence: 99%